Topical treatment of chemotherapy-induced peripheral neuropathy (CIPN) with high-concentration (179 mg) capsaicin patch in breast cancer patients – results of the QUCIP study - Lux, Michael Patrick; Flöther, Lilit; Frömter, Catrin; Rack, Brigitte; Veselinovic, Kristina; Heine, Myriam; Paepke, Stefan; Krabisch, Petra; Quandel, Tamara; Sabatowski, Rainer (Frontiers in Oncology, 2024)
BackgroundChemotherapy-induced peripheral neuropathy (CIPN) following oral or intravenous chemotherapy often results in neuropathic pain, accompanied by symptoms such tingling, burning and hypersensitivity to stimuli, with a notable decline in quality of life (QoL). Effective therapies for CIPN are lacking, with a high demand for analgesics to address this issue. The QUCIP study aimed to assess the effectiveness of high concentration (179 mg) capsaicin patch (HCCP) in alleviating neuropathic pain and associated symptoms in breast cancer patients with confirmed CIPN.MethodsQUCIP is a prospective, multi-center observational study spanning 36 weeks with up to three HCCP treatments. Initial treatment (visit V0) was followed by two telephone contacts (T1, T2) and subsequent face-to-face visits every 12 weeks or upon retreatment (visits V1–V3). 73 female patients with painful CIPN post neoadjuvant/adjuvant breast cancer therapy were enrolled. Primary endpoint was the reduction of neuropathic pain symptom score (painDETECT®). Secondary endpoints included improvements in CIPN-specific QoL (QLQ-CIPN20), reductions in pain intensity (numeric pain rating scale, NPRS), and achievement of ≥ 30% and ≥ 50% pain reduction.ResultsMedian age was 61 years, with 52.0% of patients experiencing peripheral neuropathic pain for > 1 year (> 2 years: 34.2%). The painDETECT® score significantly decreased from baseline (19.71 ± 4.69) to 15.80 ± 6.20 after initial treatment (p < 0.0001) and continued to decrease at follow-up visits. The NPRS indicated significant pain intensity reduction at each time point, particularly pronounced in patients receiving three HCCP treatments. Clinically significant pain relief of ≥ 30% increased from 25.0% at week 4 (T2) to 36.2%, 43.5%, and 40.0% at weeks 12 (V1), 24 (V2), and 36 (V3), respectively. The percentage of patients achieving pain relief of ≥ 50% increased from 14.7% at T2 to 15.5%, 21.7% and 32.5% at V1, V2 and V3, respectively. Patients further reported a significant improvement in their CIPN-related QoL throughout the study. Adverse drug reactions (ADRs) mainly included application site reactions.ConclusionIn this study, HCCP shows benefit in managing CIPN in real-world settings. The data demonstrate a sustained and progressive reduction in neuropathic pain and symptomatology, confirming the clinical benefit of repeated treatment observed in former clinical trials. HCCP treatment has also the potential to significantly improve the QoL associated with CIPN. The safety profile of HCCP was confirmed, supporting its use in clinical practice.